2005
DOI: 10.1016/j.cell.2004.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemic Effects of Dietary Saturated Fats Mediated through PGC-1β Coactivation of SREBP

Abstract: The PGC-1 family of coactivators stimulates the activity of certain transcription factors and nuclear receptors. Transcription factors in the sterol responsive element binding protein (SREBP) family are key regulators of the lipogenic genes in the liver. We show here that high-fat feeding, which induces hyperlipidemia and atherogenesis, stimulates the expression of both PGC-1beta and SREBP1c and 1a in liver. PGC-1beta coactivates the SREBP transcription factor family and stimulates lipogenic gene expression. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
465
4
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(523 citation statements)
references
References 49 publications
33
465
4
15
Order By: Relevance
“…In a similar way, it has been recently demonstrated that SFA, which induces hyperlipidemia and atherogenesis, stimulate the expression of the sterol responsive element binding protein (SREBP) (Lin et al 2005). Nevertheless, some effects of n-3 PUFA and SFA on physiological processes remain poorly defined.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar way, it has been recently demonstrated that SFA, which induces hyperlipidemia and atherogenesis, stimulate the expression of the sterol responsive element binding protein (SREBP) (Lin et al 2005). Nevertheless, some effects of n-3 PUFA and SFA on physiological processes remain poorly defined.…”
Section: Resultsmentioning
confidence: 99%
“…A strong association was observed between TRIB3 mRNA and transcript levels of the transcriptional coactivator peroxisome proliferator-activated receptor γ coactivator 1 beta (PPARGC1B, also referred to as PGC-1β, which, in contrast to PPARGC1A, has been shown to bind and directly co-activate SREBPs [11]. Despite a modest association between TRIB3 transcripts and transcripts encoding SREBP-1c, recent studies have shown that nuclear import of SREBP-1c is enhanced by endoplasmic reticulum stress, which is implicated in insulin resistance [12].…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been reported that a diet rich in saturated fat increased expression of the transcriptional co-activator PGC1b (Lin et al, 2005). This in turn was shown to enhance the transcriptional activity of SREBP1c.…”
Section: Regulation Of Gene Expression By Dietary Lipidsmentioning
confidence: 99%